Analisis Tingkat Pengetahuan Siswa tentang Potensi Bencana Tanah Longsor di Jalur Lintas Sumatera MAN 1 Sijunjung - Supaki, Eline Kurnia; Riant, Slamet; Setriani, Loli (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Sijunjung Regency is an area in West Sumatra Province with a high susceptibility to landslides, particularly along the Trans-Sumatra Highway. This situation necessitates that students possess adequate knowledge regarding mitigation measures to be taken before, during, and after a disaster. This study aims to analyze the level of student knowledge regarding landslide disaster mitigation—specifically the pre-disaster, during-disaster, and post-disaster phases—at MAN 1 Sijunjung. The study employs a quantitative approach using a descriptive method. The research population consists of all students at MAN 1 Sijunjung, with a sample of 60 students selected via total sampling. Data were collected using a disaster mitigation knowledge test comprising objective questions designed to measure students' ability to identify and determine appropriate mitigation actions for each disaster stage. The data were analyzed descriptively based on the percentage of correct answers. The results indicate that student knowledge regarding pre-disaster mitigation reached 81.66% (categorized as